PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN DAN DAMPAKNYA TERHADAP RETURN SAHAM - Welly Salipadang; Robert Jao; Beauty Beauty (Dinamika Akuntansi Keuangan dan Perbankan, 2017)
The purpose of this study was to investigate the effect of Good Corporate Governance mechanism including managerial ownership, institusional ownership, independent commissioner, and audit committees on the timeliness of financial reporting and stock return. This research represents the empirical test which used purposive sampling techniques in data collection. Data were collected using a secondary data from manufacturing company listed in Indonesian Stock Exchange 2015-2016. The results of this study indicate that the managerial ownership and institusional have a significantly and positively effect to the timeliness of corporate financial reporting. Independent commissioner and audit commitees have a positively effect but not significantly to the timeliness of corporate financial reporting. Furthermore, institusional ownership have a significantly and positively to the stock return. Managerial ownership, institusional ownership, and audit commitees have a positively effect but not significantly to stock return. But on the otherhand, the timeliness of corporate financial reporting do not have significantly and positively effect to stock return. Keywords: managerial ownership, institusional ownership, independent commissioner, audit committees, timeliness of financial reporting, and stock return